BUILDING CAFÉ CUSTOMER LOYALTY : SYNERGISTIC ANALYSIS OF SERVICE QUALITY, PRICE FAIRNESS AND WORD OF MOUTH - Negoro, Wisnu Ario; Kurniawati, Kurniawati; Masnita, Yolanda (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The purpose of this study is to examine how word-of-mouth (WOM) in Indonesia's café business is impacted by consumer attitudes, shop environment, pricing fairness, service quality, and product quality. The primary theoretical framework used in the research is the Theory of Planned Behavior (TPB), which focuses on the ways in which these factors impact consumer attitudes and word-of-mouth (WOM). Purposive sampling was used in the survey process, and 260 respondents were chosen depending on whether they had visited or made purchases from Lawson Café, McCafé, or Starbucks in the three months before. An online survey was used to gather data, and AMOS 26 software's Structural Equation Modeling (SEM) was used for analysis. The findings show that although service and product quality have no discernible effects on consumer preferences, pricing fairness and shop environment do. Favorable consumer perceptions of cafés greatly influence favorable word-of-mouth. The research also shows that fair prices and shop ambiance are important factors in influencing consumers' emotional experiences and influencing their propensity to refer friends to cafés. This study offers useful recommendations for café owners looking to improve customer experiences via marketing tactics that emphasize reasonable prices and a welcoming environment.